Application of the balanced scorecard and the cost-benefit model for evaluate of social projects - I. V. Solntsev (Управленческие науки)
Social initiatives are not always considered in the context of efficiency the solution of certain tasks often prevails, without taking into account the necessary investments or generated results. In the current crisis, when access to financial resources is extremely limited, the issue of efficiency is of particular relevance both for the state and for private investors implementing social projects. One of the most common methods for their evaluation is the balanced scorecard and the cost-benefit model. The purpose of this work is to study the features of the practical application of these tools for evaluating the effectiveness of social projects, the rationale for specific metrics, approaches to their integration into a single system, as well as consideration of some features of the calculations, for example, the justification of the social discount rate. The work used such scientific methods as analysis, comparison, generalization and modeling. The author adapts the balanced scorecard for the evaluation of social projects, explains its structure and offers a typical model that can be used regardless the field of application (health, education, sports, etc.). Today the presence of a fair evaluation system will become an important competitive advantage that makes this study interesting for government agencies at the federal and regional levels, government corporations and businesses, as well as charitable foundations.